Spectral control of power diode lasers with enhanced output by an external cavity based on a volume holographic grating - Bashchenko, S.M.; Marchenko, L.S.; Negriyko, A.M.; Smirnova, T.N.; Matsnev, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
To achieve the maximum efficiency in the single-frequency lasing mode of a laser diode with an external cavity, it is necessary to minimize losses in the optical system for the output beam and to provide the optimal frequency-selective feedback. In this paper, we have investigated the scheme of an external cavity diode laser (ECDL) based on a phase volume holographic grating (VHG). Angular and spectral selectivities of the holographic grating allow for adjusting the optical feedback with low losses in the cavity, and it can be used for the frequency narrowing of diode-array bars. Here, the optimal parameters of VHG and the temperature dependence of the diode laser bar spectrum have been studied, and the proposals on VHG design have been developed.